The Combined Use of Pediococcus pentosaceus and Fructooligosaccharide Improves Growth Performance, Immune Response, and Resistance of Whiteleg Shrimp Litopenaeus vannamei Against Vibrio parahaemolyticus - Hong, Nguyen Thi Xuan; Linh, Nguyen Thi Hue; Baruah, Kartik; Thuy, Do Thi Bich; Phuoc, Nguyen Ngoc (Frontiers in Microbiology, 2022)
In this study, we evaluated the effect of probiotic bacteria Pediococcus pentosaceus supplemented at different inclusion levels in a control diet containing 0.5% fructooligosacharide (FOS) on the growth performance, feed conversion ratio, immune response, and the disease resistance of whiteleg shrimp Litopenaeus vannamei juveniles towards Vibrio parahaemolyticus. A control 0.5% FOS added diet without supplementation of P. pentosaceus (Control), and three other experimental diets supplemented with P. pentosaceus at 1 × 106 cfu g-1 diet (P1), 1 × 107 cfu g-1 diet (P2), or 1 × 108 cfu g-1 diet (P3) were formulated. After a 60-day feeding trial, the experimental shrimps were challenged with Vibrio parahaemolyticus. The results showed that dietary supplementation of P. pentosaceus significantly improved the growth performance and immune responses of L. vannamei juveniles. The juveniles that were fed with a diet supplemented with P. pentosaceus at 1 × 107 cfu of g-1 diet (P2) or 1 × 108 cfu g-1 diet (P3) recorded the maximum increase in the final body weight, final length, weight gain (WG), survival rate, total haemocyte counts (THC), phenoloxidase, and lysozyme activity. The results also showed that juveniles fed with a P2 or P3 diet exhibited significantly lower mortality when challenged with V. parahaemolyticus. Overall results suggested that a combination of P. pentosaceus at the inclusion level of 1 × 107 cfu g-1 diet (P2) and 0.5% FOS could be considered as a potential synbiotic formulation for improving the growth, health, and robustness of L. vannamei.